Juggling to find balance: hearing the voices of undergraduate student nurses. (13th August 2020) - Mills, Anne; Ryden, Julie; Knight, Anneyce
Abstract : Background: Accounts of stress are common among students on nursing programmes. Prolonged high levels of stress can contribute to poor learning, the development of detrimental health behaviours, attrition and burnout. Aims: To examine the health and wellbeing implications of undertaking a BSc nursing degree in the UK for first-year students. Methods: Qualitative narrative analysis of 100 written student reflections on the influences on their health and wellbeing was undertaken. Findings: Nursing students must juggle multiple competing demands on their physical capabilities, personal resources, income and time. Students are constantly seeking to achieve balance and personal equilibrium through the use of a variety of coping strategies. Conclusion: This work calls upon the profession, the nursing regulator, nursing programmes within higher education institutions and health Trusts to review the framework and content of undergraduate BSc nurse education. Programme requirements should enhance the health and wellbeing of students while simultaneously delivering education and practice opportunities necessary to meet professional requirements.